Role of Non-Invasive Mechanical Ventilation for Acute Respiratory Failure in Cancer Patients - Basnet, Madindra Bahadur; Acharya, Krishna Prasad; Adhikari, Deepak (Nepalese Medical Journal, 2020)
Introduction: Acute respiratory failure is a common cause of Intensive care Unit admission for cancer patients. Non-invasive ventilation comes in between the two extreme situations: either provide only oxygen or ventilate invasively. This study was done to find the usefulness and efficacy of non-invasive ventilation in a cancer patient. Materials and Methods: A cross-sectional study was done at Nepal Cancer Hospital. Data analysis of patients requiring non-invasive ventilation at the Intensive care Unit from April 14, 2018, to April 13, 2019, were included. Results: Among 68 studied patients, the primary reason for the initiation of non-invasive ventilation sepsis (16.32%), pneumonia (10.88%), and lung cancer (10.2%). Postoperative atelectasis, pulmonary edema, and morphine overdose were associated with good respiratory improvement and Intensive care Unit survival (100%, 75% and 66.67% respectively). Respiratory failure with carcinoma lung, lung fibrosis, acute respiratory distress syndrome, terminally ill patients, and patients with low Glasgow Coma Scale had high failure rates (Survival: 13.33%, 14.29%, 16.67%, 0%, and 20% respectively). Conclusions: Non-invasive ventilation seems to be an effective way of ventilation for cancer patients. The selection of patients and timely initiation of non-invasive ventilation is of utmost importance for a better outcome.